What do arc magmatism trace-element patterns and Sr–Nd–Pb isotopic data reflect? Insights from the Urumieh–Dokhtar magmatic arc of Iran - M. R. Ghorbani; M. Akbari; M. Akbari; I. T. Graham; M. Benoit; F. Sepidbar (Solid Earth)
Mafic volcanic rocks from the Cenozoic Urumieh–Dokhtar magmatic arc (UDMA) of Iran, a segment of the Alpine–Himalayan orogenic belt, provide rather restricted ranges of trace-element abundances and patterns as well as Sr–Nd–Pb isotopic signatures. However, they are distinct enough to help characterize the geochemical signatures inherited from their arc system components. The volcanic rocks are classified into three series: the LILE-rich, LILE-poor, and incompatible trace-element-rich series (ITE-rich series, which includes samples with OIB-like – oceanic-island basalt – patterns). The LILE-rich series is derived from a mantle source metasomatized by fluid-rich slab partial melts, whereas the LILE-poor series, high in immobile and highly incompatible elements that include La and Ce, is derived from a mantle source metasomatized by fluid-poor slab partial melts. Slab melting is favored by the young, hot slab subduction of a then narrow, contracting Neotethyan oceanic plate. The ITE-rich series bear the signatures of mantle metasomatized by slab partial melts that were induced by, and reacted with, asthenospheric mantle that ascended through a slab window or rupture. Given almost primitive geochemical signatures of the mafic rocks, the Sr–Nd isotopic modeling indicates mantle wedge : slab melt : sediment melt contributions of 45:27.5:27.5<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="73pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="ce935418d84fa60f14ff0e83f2468c45"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-663-2025-ie00001.svg" width="73pt" height="10pt" src="se-16-663-2025-ie00001.png"/></svg:svg> and 55:09:36<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="a55ddcf581afa01ca391c0c927ba34e5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-663-2025-ie00002.svg" width="54pt" height="10pt" src="se-16-663-2025-ie00002.png"/></svg:svg> for the LILE-rich and LILE-poor series respectively. The mafic volcanic rocks, which extend from the mantle array (i.e., the NHRL; Northern Hemisphere reference line) toward an enriched mantle, on the Pb–Pb isotopic plots, further support this finding. Eocene to Early Miocene ages for these three series favor intermittent volcanism of each rock series over an extended period of time, rather than single episodic magmatism for each geochemically distinct magma series. Dominance of LILE-rich series rocks in the northern part of the study area (the Kahak area) points to a more hydrous, more altered slab compared to the slab beneath the central part, where the LILE-poor series is dominant.